2019
DOI: 10.1101/562371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverted translational control of eukaryotic gene expression by ribosome collisions

Abstract: The canonical model of eukaryotic translation posits that ef cient translation initiation increases protein expression and mRNA stability. Contrary to this dogma, we show that increasing initiation rate can decrease both protein expression and stability of certain mRNAs in the budding yeast, S. cerevisiae. These mRNAs contain a stretch of poly-basic residues that cause ribosome stalling. Using computational modeling, we predict that the observed decrease in gene expression at high initiation rates occurs when … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…If the presence of polybasic sequences represents an important obstacle to translation, we expect to find signatures of poor translatability in proteins that contain them. For example, endogenous genes containing stall sequences have a slower or less efficient translation initiation; this is thought to be an adaptation to avoid ribosome collision during elongation [32]. Therefore, we asked whether the polybasic and the ICP data sets would be significantly different from the rest of the yeast genes in experimental measurements that reflect translation activity.…”
Section: Proteins With Polybasic Sequences Show Divergent Patterns Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…If the presence of polybasic sequences represents an important obstacle to translation, we expect to find signatures of poor translatability in proteins that contain them. For example, endogenous genes containing stall sequences have a slower or less efficient translation initiation; this is thought to be an adaptation to avoid ribosome collision during elongation [32]. Therefore, we asked whether the polybasic and the ICP data sets would be significantly different from the rest of the yeast genes in experimental measurements that reflect translation activity.…”
Section: Proteins With Polybasic Sequences Show Divergent Patterns Ofmentioning
confidence: 99%
“…Different studies have shown that the existence of stalling features in endogenous sequences seems to be accompanied by other unique characteristics, such as low initiation efficiency [31,32] and/or the positioning of the stall sequence at the beginning of the transcript [33]. These adaptations are thought to result in fewer ribosomes per transcript, which would avoid ribosome collisions at the stalling-prone segments, thus preventing RQC activation.…”
Section: Introductionmentioning
confidence: 99%
“…To monitor gene expression, series of methodologies have been well developed from small-scale ones such as Northern blotting ( Krumlauf, 1994 ), qRT-PCR ( Nolan et al, 2006 ) and Western blotting ( Burnette, 2011 ), to genome-wide ones such as microarray analysis ( Slonim and Yanai, 2009 ), transcriptome ( Zhang et al, 2018b ) and protein sequencing ( Timp and Timp, 2020 ). In contrast, the methodology that can directly evaluate mRNA translation is still greatly limited, though the crucial roles of translation regulation in gene expression have been well documented ( Istomine et al, 2016 ; Merchante et al, 2017 ; Zhang et al, 2018c ; Moissoglu et al, 2019 ; Park and Subramaniam, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the protein coding region has been recently recognized as a critical determinant of eukaryotic mRNA stability (2,3). The role of the coding sequence in mRNA stability is best understood in the budding yeast S. cerevisiae where poorly translated codons and nascent peptide motifs with positively charged residues can destabilize mRNAs (4)(5)(6)(7). Poorly translated codons have also been implicated in regulation of mRNA stability in several other organisms (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%